UPAYA MENINGKATKAN KEMAMPUAN MELOMPAT MELALUI GERAK IRAMA BAGI ANAK TUNAGRAHITA SEDANG - Hairi - Diana (Universitas Negeri Padang, 2014)
The background this research was, there is a child who can not read the word jump at SLB N 1 Padang. Jump Techniques is manner a child for happy reading, the purpose of this study is to prove the effectiveness of jump in improving the reading skills for tunagrahita medium child at 1 Padang. Type of study is a Single Subject Research with A-B-A desaign. The results of this study is jumping techniques effective to go up of read the word dual vocals for a tunagrahita medium child at SLBN 1 Padang.